Public Interest in Medical Research Participation: Differences by Volunteer Status and Study Type. Issue 2 (23rd January 2014) - Cobb, Enesha M.; Singer, Dianne C.; Davis, Matthew M.
Abstract: Purpose: We assessed national levels of public interest in medical research participation (MRP) and factors associated with interest as a healthy volunteer; as a diagnosed volunteer; and in seven study types. Method: Cross‐sectional, Web‐based survey of the US population in June 2012. Descriptive statistics estimated interest in MRP and multivariable logistic regression determined associations between respondent‐level predictors and interest in MRP. Results: Of 2, 668 respondents (response rate = 61%), 41% were interested in MRP as healthy volunteers and 60% as diagnosed volunteers. Respondents with some college (OR = 1.54, 1.09–2.19) or higher education (OR = 1.86, 1.29–2.70) had higher adjusted odds of interest as healthy volunteers. Non‐Hispanic black race (OR = 0.56, 0.37–0.86) and education below high school (OR = 0.57, 0.35–0.92) were associated with lower adjusted odds of interest as diagnosed volunteers. Non‐Hispanic black race was associated with lower odds of interest in medication trials as diagnosed volunteers (OR = 0.61, 0.40–0.93). Conclusions: We found high levels of interest in MRP that contrast with low levels of prior research participation. Interest is higher in medical research involving noninvasive designs. Comparatively lower levels of interest in MRP among non‐Hispanic blacks and those with less education raise concerns about disparities in future study enrollment.